Geographical information systems: An effective planning and decision making platform for community health coalitions in Australia - Baum, S.; Kendall, E.; Muenchberger, H.; Gudes, Ori; Yigitcaniar, T. (Health Information Management Association of Australia, 2010)
The development of locally-based healthcare initiatives, such as community health coalitions that focus on capacity building programs and multi-faceted responses to long-term health problems, have become an increasingly important part of the public health landscape. As a result of their complexity and the level of investment, it has become necessary to develop innovative ways to help manage these new healthcare approaches. Geographical Information Systems (GIS) have been suggested as one of the innovative approaches that will allow community health coalitions to better manage and plan their activities. The focus of this paper is to provide a commentary on the use of GIS as a tool for community coalitions and discuss some of the potential benefits and issues surrounding the development of these tools.